A Comparison of the Effects of Continuous Illumination and Day/Night Regimes on PHB Accumulation in Synechocystis Cells - Fleischhacker-Daffert, Christina; Zerobin, Antonia; Hummel, Ferdinand; Slaninova, Eva; Kroupová, Zuzana; Obruca, Stanislav; Mrazova, Katerina; Hrubanova, Kamila; Krzyzanek, Vladislav; Nebesarova, Jana; Ludwig, Katharina; Fritz, Ines (Life (Basel, Switzerland), 2024)
Poly(3-hydroxybutyrate) (PHB) is a biobased and biodegradable polymer with properties comparable to polypropylene and therefore has the potential to replace conventional plastics. PHB is intracellularly accumulated by prokaryotic organisms. For the cells PHB functions manly as carbon and energy source, but all possible functions of PHB are still not known. Synechocystis (cyanobacteria) accumulates PHB using light as energy and CO2 as carbon source. The main trigger for PHB accumulation in cyanobacteria is nitrogen and phosphorous depletion with simultaneous surplus of carbon and energy. For the above reasons, obtaining knowledge about external factors influencing PHB accumulation is of highest interest. This study compares the effect of continuous light exposure and day/night (16/8 h) cycles on selected physiology parameters of three Synechocystis strains. We show that continuous illumination at moderate light intensities leads to an increased PHB accumulation in Synechocystis salina CCALA 192 (max. 14.2% CDW - cell dry weight) compared to day/night cycles (3.7% CDW). In addition to PHB content, glycogen and cell size increased, while cell density and cell viability decreased. The results offer new approaches for further studies to gain deeper insights into the role of PHB in cyanobacteria to obtain bioplastics in a more sustainable and environmentally friendly way.
Keywords: PHB; glycogen; day/night cycle; cell size; Synechocystis; continuous illumination